PENDIDIKAN REKONSTRUKSIONISME SEBAGAI LANDASAN FILOSOFIS REFORMASI KURIKULUM DI ERA GLOBALISASI - Khaafidlotun Nisa’; Selsa Yulianingsih; Nunung Asni; Muhlisin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Curriculum reform in the globalization era requires a philosophical foundation capable of responding to social dynamics, technological advancement, and moral challenges holistically. Reconstructionism, as a philosophy of education that positions education as an agent of social change, offers a relevant conceptual framework to address these needs. This study aims to analyze the concept of reconstructionism as a philosophical foundation for curriculum reform in Indonesia and its implications for national curriculum design and development. The method used is library research with a descriptive-qualitative approach through thematic analysis of 22 academic literature sources and 3 national curriculum policy documents from the period 2018–2025. The results show that the principles of reconstructionism such as orientation toward social transformation, strengthening humanitarian values, and active student participation in solving societal problems are in line with the spirit of curriculum reform in Indonesia, particularly in the Merdeka Curriculum. However, its implementation still faces challenges such as infrastructure gaps, educator readiness, and low digital literacy. It is concluded that reconstructionism can serve as a strong philosophical foundation for adaptive, contextual, and character-oriented curriculum reform, preparing Indonesians to face global challenges.